Assessing genotypic diversity in Gladiolus grandiflorus for tolerance to saline conditions - AMALA, EDIGA; SWAROOP, KISHAN; SINGH, KANWAR PAL; PANWAR, SAPNA; SHARMA, V K; PRASAD, SHIV; SOLANKE, AMOLKUMAR U; NAMITA; SANGMESH, PANCHAL (The Indian Journal of Agricultural Sciences, 2025)
Salinity is a major abiotic stress affecting crop productivity, particularly in commercial cut flower like gladiolus (Gladiolus grandiflorus L.), which is highly sensitive. The present study was carried out during 2022–23 and 2023–24 at ICAR-Indian Agricultural Research Institute, New Delhi to evaluate the morphological, physiological and biochemical responses of 10 gladiolus genotypes (Peter Pears, Pusa Red Valentine, Warang Pink, Pusa Srijana, Urmi, Little Fawn, Urvashi, Gulal, Pusa Suhagin and Yellow Stone) under different salinity levels (0, 45 and 90 mM NaCl). Growth parameters, including plant height (22.1%), leaf area (37.8%) and number of corms (22.17%) were significantly reduced due to highest salinity stress level (90 mM NaCl) and it varied with the genotypes. Genotypes Little Fawn and Yellow Stone exhibited superior performance, maintaining higher relative water content (86.22 and 83.75%, respectively) at 90 mM NaCl, while chlorophyll levels (declined up to 10.5% at 45 mM and 23.4% at 90 mM NaCl) compared to more salinity sensitive genotypes like Pusa Srijana (68.1% reduction in RWC and 55.8% reduction in total chlorophyll). The salinity-induced oxidative stress, indicated by increased electrolyte leakage rate (83.3% in Little Fawn and 443.7% in Pusa Srijana) and malondialdehyde content (108.1%), were notably lower in the tolerant genotypes. Principal component analysis (PCA) revealed a strong correlation between growth traits and stress bio-markers, highlighting the resilience of Little Fawn and Yellow Stone. These results demonstrated the potential of selecting and evolving salt-tolerant gladiolus genotypes, offering a pathway for sustainable cultivation in salt-affected areas, thereby supporting the flower industry.